Conservation of the intangible: a continuing challenge. Issue 1 (December 2014) - Wain, Alison
Abstract : Western concepts of heritage conservation have traditionally centred on tangible heritage. This material focus has been challenged in recent decades by a new focus on intangible heritage, which has been recognised both as being a cultural production of value and significance in its own right, and as having a fundamental role in the identification and survival of tangible heritage. To respond effectively to these changes in conceptions of heritage, conservators are required to extend their understanding and practice to address the challenges of conserving intangible heritage, including eliciting stakeholder values and understanding and supporting the preservation of embodied knowledge through continued performance. Non-Western communities, and conservators working with non-Western heritage, have been particularly active in developing protocols for dealing with intangible heritage. This paper argues that conservators working with heritage from all cultures need to equally recognise the importance of intangible heritage, and to develop protocols for conserving and managing it that are relevant to their areas of cultural expertise.